1986
DOI: 10.1002/ana.410190419
|View full text |Cite
|
Sign up to set email alerts
|

Progressive multifocal leukoencephalopathy and magnetic resonance imaging

Abstract: Progressive multifocal leukoencephalopathy developed in a homosexual man with underlying Hodgkin's disease. Computed tomography and magnetic resonance imaging of the brain demonstrated multiple lesions, more in gray than white matter. Brain biopsy established the diagnosis of progressive multifocal leukoencephalopathy. Magnetic resonance imaging was found useful for detecting brain lesions and for localizing an accessible lesion for biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…The symptoms and signs of PML in patients with other underlying immunodeficiencies are similar to those reported in PML associated with AIDS (2,28–31). The symptoms of PML most commonly include motor weakness (42%), speech abnormalities (40%), cognitive abnormalities (36%), headache (32%), visual field deficits (32%), ataxia (21%), aphasia (17%), cranial nerve deficits (13%) and sensory deficits (9%) (2,28,29,32–37).…”
Section: Discussionsupporting
confidence: 75%
“…The symptoms and signs of PML in patients with other underlying immunodeficiencies are similar to those reported in PML associated with AIDS (2,28–31). The symptoms of PML most commonly include motor weakness (42%), speech abnormalities (40%), cognitive abnormalities (36%), headache (32%), visual field deficits (32%), ataxia (21%), aphasia (17%), cranial nerve deficits (13%) and sensory deficits (9%) (2,28,29,32–37).…”
Section: Discussionsupporting
confidence: 75%
“…MRI patterns in PML are widely recognised and reveal multifocal lesions of cerebral white matter, with few specific elements [7][8][9]. Accordingly, the diagnosis of PML is based on identification by PCR of viral sequences in the CSF.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the increased prevalence of PML, many aspects of this disease, including the pathology, clinical characteristics and radiological findings, have become known [19][20][21]. It has been suggested that the JCV circulating in the human population is an archetypal strain that can establish latency in the kidneys [22,23].…”
mentioning
confidence: 99%